Caspr2 antibodies in patients with thymomas. - Vincent, A; Irani, SR (2010)
Myasthenia gravis is the best known autoimmune disease associated with thymomas, but other conditions can be found in patients with thymic tumors, including some that affect the central nervous system (CNS). We have become particularly interested in patients who have acquired neuromyotonia, the rare Morvan disease, or limbic encephalitis. Neuromyotonia mainly involves the peripheral nerves, Morvan disease affects both the peripheral nervous system and CNS, and limbic encephalitis is specific to the CNS. Many of these patients have voltage-gated potassium channel autoantibodies. All three conditions can be associated with thymomas and may respond to surgical removal of the underlying tumor together with immunotherapies and symptomatic treatments. Herein, we review the results of our recent studies that show that voltage-gated potassium channel autoantibodies are not principally directed against the potassium channels themselves but in some patients are directed against a protein that is complexed with potassium channels in both the peripheral nervous system and CNS, contactin-2 associated protein (Caspr2). These antibodies are common in the subgroup of patients with thymic malignancies.